Application Research Progress of Nanomaterial Graphene and its Derivative Complexes in Tumor Diagnosis and Therapy - Cui, Li Wen; Fan, Lu Yao; Shen, Zhi Yong (Current Medicinal Chemistry, 2024)
Functional nanomaterial graphene and its derivatives have attracted considerable attention in many fields because of their unique physical and chemical properties. Most notably, graphene has become a research hotspot in the biomedical field, especially in relation to malignant tumors. In this study, we briefly review relevant research from recent years on graphene and its derivatives in tumor diagnosis and antitumor therapy. The main contents of the study include the graphene-derivative diagnosis of tumors in the early stage, graphene quantum dots, photodynamics, MRI contrast agent, acoustic dynamics, and the effects of ultrasonic cavitation and graphene on tumor therapy. Moreover, the biocompatibility of graphene is briefly described. This review provides a broad overview of the applications of graphene and its derivatives in tumors. Conclusion, graphene and its derivatives play an important role in tumor diagnosis and treatment.
Keywords: photodynamic